Implikasi Hukum dan Keadilan Atas Terbitnya Regulasi Penyerahan Prasarana, Sarana, dan Utilitas Perumahan di Kota Yogyakarta - SAKUNDIANA, VITA DWI (Program Studi Hukum Universitas Pamulang, 2025)
The handover of Infrastructure, Facilities, and Public Utilities (PSU) by developers to the Yogyakarta City Government is a legal obligation intended to ensure the sustainability of infrastructure management and the maintenance of environmental quality in residential areas. The issuance of Yogyakarta Mayor Regulation Number 31 of 2024 is an important step in clarifying the mechanism for handing over PSUs which previously did not have legal certainty. This study aims to analyze the legal implications of the regulation on developers, the Yogyakarta City Government, and housing residents, and assess the extent to which the principles of distributive, procedural, and social justice are reflected in the handover of PSUs in the City of Yogyakarta. This study applies a normative and empirical legal approach method by examining related laws and regulations and conducting in-depth interviews with the Yogyakarta City DPUPKP, developers, and representatives of housing residents. The data was analyzed qualitatively descriptively to relate regulations to conditions in the field. The results of the study show that this regulation closes the legal vacuum in PSU governance, strengthens the legitimacy of the Yogyakarta City Government in receiving and managing PSU assets, and provides legal certainty and protection of rights for housing residents. This regulation also realizes: 1) the principle of distributive justice through a proportionate division of responsibilities between developers, governments, and housing residents; 2) procedural fairness through clear verification and documentation mechanisms; and 3) social justice through the recognition of PSUs as public facilities that can be accessed by all housing residents adequately and functionally. Thus, this mayoral regulation plays an important role as an important instrument in realizing fair and sustainable formal housing governance, while strengthening legal certainty for all related parties.